Academic Senate Minutes 2009-05-21 - Academic Senate:::::::::
Agenda approved. Chair Report. Approval of Minutes of 4/23/09. Bioengineering concentration and Management streamline curriculum proposals approved. Candidates for Graduation approved. Special Report: Academic Council on International Programs. Revision to Withdrawal from Courses policy – Approved. Revision to Course Repeat policy – Approved. Revisions to the Academic Probation, Disqualification and Probation policy. Approved. University Strategic Plan endorsed. Nominations to the Executive Committee. Resolution extending the work of the Senate's Ad-Hoc Diversity Committee to October 1, 2009 approved. Resolution congratulating Dr. Jeffrey Reeder for being named Bike Commuter of 2009 approved. President Report. Changing of the Guard